Analisis dalam Pemberitaan Pro Dan Kontra Terhadap Lahirnya UU ITE (Undang-Undang Informasi dan Transaksi Elektronik) dan Kaitannya dengan Teori Demokrasi di Indonesia - Bayu Septiyan; Ainur Ropik; Hatta Azuhri (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study is conducted for the purpose of analyzing the Pros and Cons of Reporting on the Birth of the UU Ite (Electronic Information and Transaction Law) in Indonesia and will focus on finding out how the pros and cons of the ITE Law (Electronic Information and Transaction Law) promulgated. in Indonesia? The increasingly rapid development of information and communication technology makes the community more active in it, and from this the law will not remain silent, this activity has been regulated in cyber law, which is described in the Constitution Number 11 of 2008 concerning Information and Electronics. This law is known as the ITE Law. This study uses a qualitative descriptive method, the data used are sourced from literature studies related to theories on the internet as well as journals and books, besides that the researchers also conduct observations, while the data analysis is inductive/qualitative, and the research results Qualitative research emphasizes meaning more than generation. The results of this study are that the pro and contra of the issuance of the Electronic Information and Transactions Law (ITE) in Indonesia is still a great debate among the Indonesian people, some people think that the existence of the Electronic Information and Transactions Law (ITE) can lead to several good benefits including: the public is more careful in commenting on social media which usually contains excessive hate speech, and the regularity of the public speaking space. Information and Electronic Transactions (ITE) are considered to affect democracy in Indonesia, they consider the Law on Information and Electronic Transactions (ITE) to limit their freedom of expression on social media by existing laws. They consider democracy no longer running properly and the level of democracy in Indonesia. a relative decrease Keywords: ITE Law, News, Democracy, Pros and Cons